Bank Financial Capability on MSME Lending Amid Economic Change and The Growth of Fin-Tech Companies in Indonesia - Wibowo, Martino; Aumeboonsuke, Vesarach (Thailand and The World Economy, 2020)
Abstract This paper studies ten years (2008-2018) of annual financial data from four state-owned banks, macroeconomic data and data from the financial technology (fin-tech) industry using ratio analysis, dynamic estimation and common size statements analysis. The study also considers the analysis of independent attributes such as macroeconomic factors, for example, GDP growth, inflation, interest rates and fin-tech lending supply that could affect the financial performance of the banks. On the other hand, this research emphasizes that competition with fin-tech companies could affect bank performance and the capacity to supply loans. In general, the results show that most of the banks are still capable and comply with supply lending to MSMEs as mandated by the regulation in the short term. However, in the long term, the intention is moving slowly and tends to decrease - possibly due to the dynamics of economic growth and the development of financial technology companies.